The Effect of Health Promotion Using Animation Media and Lessons on Adolescent Knowledge About Reproductive Health at SMAN 1 Suela Lombok Timur - Nurlathifah N. Yusuf; Siti Naili Ilmiyani; Supiani (PT Inovasi Pratama Internasional, 2023)
The condition of adolescents who are vulnerable to being the target of risky behavior problems such as unwanted pregnancies, early marriages, and abortions requires serious treatment in preventing these negative behaviors so innovation is needed to carry out health promotion that can attract adolescents' interests. Health promotion using animation media is packaged in the form of short videos with a simple and fun storyline approach. The purpose of this study was to determine the effect of health promotion using animation and lecture media on young women's knowledge of reproductive health at SMAN 1 Suela East Lombok. This type of research is quasi-experimental research, with a pretest-posttest control group design. The population of this study was all female students at SMAN 1 Suela with a sample of 118 people, who were taken using a cluster random sampling technique. The students were divided into 2 groups, the experimental group would be educated with animation media, while the control group would be educated with lectures. Data analysis used in this study was univariate analysis to determine the effect before and after being given animated media and lectures using the Paired Sample T Test, and bivariate analysis to determine differences in the effectiveness of animated media and leaflets using an independent sample T-Test . The results showed that the results of the independent T-test showed that there were differences in the effect of increasing knowledge, when compared to the two media, animation media was more effective than lectures in increasing adolescent knowledge about reproductive health at SMAN 1 Suela East Lombok based on a p-value of 0.0001 <0. 05. The average value (mean) produced by animation media is 24,000, which is higher than the average value (mean) of lectures with a mean value of 13,016.